Historical insights for ebook design. Issue 4 (21st November 2016) - Koh, HyunSeung; Herring, Susan C.
Abstract : Purpose: The purpose of this paper is to provide ebook designers and researchers with design insights by promoting historical knowledge about books and reading as sources of ideas to implement in current and future ebooks. Design/methodology/approach: The authors review historical features of books and practices of reading that have been implemented, weakened, or lost over time, referring to historical texts and resources, and relate them to ebook viewers (software) and readers (hardware) that are currently on the market. In particular, the review focuses on the physical form of the book and the practices of reading, annotation, and bookshelving. Findings: While some older forms and reading practices have been implemented in ebook devices, others have been forgotten over time, due in part to physical constraints that are no longer relevant. The authors suggest that features that constrained print books and print reading in the past might actually improve the design of ebooks and e-reading in the present. Research limitations/implications: This review is necessarily based on a limited set of existing historical sources. Practical implications: Translating insights into novel tangible designs is always a challenging task. Ebook designers can gain insights from this paper that can be applied in a variety of design contexts. Originality/value: No previous work on ebook design has foregrounded historical aspects of books and reading as viable sources of ideas to implement in ebooks.